2009
DOI: 10.1080/02705060.2009.9664261
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Channel Darter (Percina copelandi) Summer Habitat in Two Rivers from Eastern Canada

Abstract: We characterized the summer habitat frequented by the channel darter (Percina copelandi) in the Gatineau River and the Richelieu River of southwest Quebec. Water velocity was the only explicative variable the two rivers had in common. The channel darter showed a strong preference for environments with mean water velocities between 39 and 48 cm.il. Moreover, the presence of periphyton in the Gatineau River, presenting high substrate heterogeneity, and the presence of woody debris and plant cover in the Richelie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Adults, in contrast, have been sampled more frequently. In streams or rivers, adult Channel Darter can be found in moderate flows (Boucher et al 2009;Boucher and Garceau 2010a) where riffles transition into deep, sand-bottomed runs or pool habitat (Reid et al 2005); alternatively, in lakes, Reid and Mandrak (2008) captured adults in beach habitat of Lake Erie consisting of coarse sand and fine gravel substrates. Lane et al (1996) identified that Channel Darter had strong associations with gravel and sand substrates, and a moderate association with silt substrate.…”
Section: Lawrence River Dusmentioning
confidence: 99%
“…Adults, in contrast, have been sampled more frequently. In streams or rivers, adult Channel Darter can be found in moderate flows (Boucher et al 2009;Boucher and Garceau 2010a) where riffles transition into deep, sand-bottomed runs or pool habitat (Reid et al 2005); alternatively, in lakes, Reid and Mandrak (2008) captured adults in beach habitat of Lake Erie consisting of coarse sand and fine gravel substrates. Lane et al (1996) identified that Channel Darter had strong associations with gravel and sand substrates, and a moderate association with silt substrate.…”
Section: Lawrence River Dusmentioning
confidence: 99%